Upaya Meningkatkan Pemahaman Eksplorasi Karir Melalui Layanan Bimbingan Kelompok dengan Teknik Diskusi Kelompok - Priyatno, Tovik (Universitas Ahmad Dahlan, 2016)
This study aims to determine the understanding improvement of career exploration through group guidance services with a group discussion technique. This study uses classroom action research conducted in two cycles. The research subjects are eight students of grade IX E SMP Muhammadiyah 7 Yogyakarta, taken by using purposive sampling. Data collection instruments use understanding questionnaires of career exploration and observation guidelines. An understanding of the students career exploration before and after group guidance services group by group discussion techniques were analyzed using t-test formula. Results of data analysis obtained by value t = 7.812> t table (1.895), with the results mean score of 119.87 pretest and posttest mean score increased to 155.75. The results of this study concluded there is an understanding improvement of career exploration through group guidance services with the student a group discussion technique. The results of this study can be used as information for guidance and counseling teachers in an effort to improve the understanding of students career exploration through group guidance services by utilizing the technique of a group discussion.